Vaccine Hesitancy and Acceptance: The Present and the Future - Sherri Sheinfeld Gorin (Vaccines)
In the following Special Issue of Vaccines, entitled “Acceptance and Hesitancy in Vaccine Uptake,” seventeen diverse papers examine the critical role of vaccination in health promotion and disease prevention [...]